Four novel variants identified in the ACADVL gene causing very-long-chain acyl-coenzyme A dehydrogenase deficiency in four unrelated Chinese families - Li, Lulu; Tang, Yue; Zhao, Jinqi; Gong, Lifei; Yang, Nan; Wang, Shunan; Yang, Haihe; Kong, Yuanyuan (Frontiers in Genetics, 2024)
Background: The biochemical and genetic characteristics of four very-long-chain acyl-coenzyme A dehydrogenase deficiency (VLCADD) patients, clarifying their pathogenic genetic factors and evaluating the application value of genetic diagnosis in the early diagnosis of VLCADD, are reported and discussed in this article. Methods: Patients underwent blood tandem mass spectrometry (MS/MS), urine gas chromatography (GC/MS), and high-throughput sequencing technology. New variants were analyzed for pathogenicity using bioinformatics software. Swiss-PdbViewer software was used to predict the effect of variants on the structure of the very-long-chain acyl-CoA dehydrogenase (VLCAD) protein. Result: A total of four VLCADD patients were diagnosed. They revealed elevated levels of C14, C14:1, C14:2, C14:1/C2, C14:1/C10, and C14:1/C12:1. Two patients were early-onset neonatal cases and died during infancy and the neonatal period, respectively. Seven kinds of variants were detected, including four novel variants. Bioinformatics software revealed that the variants were harmful, and the Swiss-PdbViewer results suggest that variation affects protein conformation. Conclusion: This study identified four novel ACADVL gene variants. These findings contribute to the understanding of the genetic basis and pathogenesis of VLCADD. Meanwhile, the study enriches the genetic mutation spectrum and the correlation between genotypes and phenotypes of VLCADD, indicating that genetic diagnosis plays an essential role in the early diagnosis and treatment of VLCADD.